2020
DOI: 10.1080/07448481.2020.1763366
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing ACT daily as a self-guided app for clients waiting for services at a college counseling center: A pilot study

Abstract: Objective: Considering increasing demands for mental health services at college counseling centers (CCCs), there is a need for cost-effective solutions that avoid depleting stressed CCC resources. This study examined if ACT Daily, a mobile application based on acceptance and commitment therapy (ACT), could serve as an effective self-guided intervention. Participants: 11 individuals on a CCC waitlist suffering from anxiety/depression participated in the study over 2 weeks. Methods: This study implemented a pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…Eleven studies are randomized controlled trials (RCT) (Witkiewitz et al, 2014 ; Gajecki et al, 2017 ; Harrer et al, 2018 ; Lee and Jung, 2018 ; Fish and Saul, 2019 ; Huberty et al, 2019 ; Bruehlman-Senecal et al, 2020 ; Flett et al, 2020 ; McCloud et al, 2020 ; Newman et al, 2020 ; Ponzo et al, 2020 ) and two studies are considered quasi-experimental trials (Benton et al, 2016 ; Borjalilu et al, 2019 ). Four studies considered a single-arm pre-test-post-test study design (Jackson et al, 2016 ; Leonard et al, 2017 ; Haeger et al, 2020 ; Lattie et al, 2020 ; Reyes et al, 2020 ) and one study included two groups through an iterative process (Kazemi et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies are randomized controlled trials (RCT) (Witkiewitz et al, 2014 ; Gajecki et al, 2017 ; Harrer et al, 2018 ; Lee and Jung, 2018 ; Fish and Saul, 2019 ; Huberty et al, 2019 ; Bruehlman-Senecal et al, 2020 ; Flett et al, 2020 ; McCloud et al, 2020 ; Newman et al, 2020 ; Ponzo et al, 2020 ) and two studies are considered quasi-experimental trials (Benton et al, 2016 ; Borjalilu et al, 2019 ). Four studies considered a single-arm pre-test-post-test study design (Jackson et al, 2016 ; Leonard et al, 2017 ; Haeger et al, 2020 ; Lattie et al, 2020 ; Reyes et al, 2020 ) and one study included two groups through an iterative process (Kazemi et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate trial design, and any deviates from the standard RCT accounted for in the conduct and analysis of the trial 11/11 2016; Borjalilu et al, 2019). Four studies considered a singlearm pre-test-post-test study design (Jackson et al, 2016;Leonard et al, 2017;Haeger et al, 2020;Lattie et al, 2020;Reyes et al, 2020) and one study included two groups through an iterative process (Kazemi et al, 2018). Eleven of the included studies are RCTs and the total sample size ranges from 72 to 330 college student participants; the overall duration of the intervention range from 14 days to 3 months and when we consider follow-ups, the longest trial lasted for 9 months.…”
Section: /11mentioning
confidence: 99%
“…A nonrandomized study design was used to examine the effectiveness, acceptability, or feasibility of nine MHapps across nine articles [18,[43][44][45][46][47][48][49]. Researchers generally adopted a quasi-experimental design obtaining pre and post-test data.…”
Section: Nonrandomized Studiesmentioning
confidence: 99%
“…Researchers generally adopted a quasi-experimental design obtaining pre and post-test data. Five studies reported preliminary findings from pilot or feasibility research [34,45,[48][49][50]. Participants were generally recruited online (k = 5).…”
Section: Nonrandomized Studiesmentioning
confidence: 99%
See 1 more Smart Citation